Psoriasis Increased the Risk of Adverse Cardiovascular Outcomes: A New Systematic Review and Meta-Analysis of Cohort Study - Liu, Lu; Cui, Saijin; Liu, Meitong; Huo, Xiangran; Zhang, Guoqiang; Wang, Na (Frontiers in Cardiovascular Medicine, 2022)
Background Several studies have investigated the relationship between psoriasis and adverse cardiovascular outcomes. Previous meta-analyses have shown psoriasis to be a risk factor for adverse cardiovascular outcomes. However, the relationship has become uncertain with the emergence of many new studies. Objective This study aimed to conduct an updated meta-analysis on cohort studies about the relationship between psoriasis and adverse cardiovascular outcomes. Methods Electronic databases (accessed till January 2022) were searched systematically for cohort studies assessing the cardiovascular risk in psoriasis patients. This was a meta-analysis using a random-effect model; pooled analyses of several cardiovascular outcomes were also conducted. Results A total of 31 [hazard ratio (HR), 23; rate ratio (RR), 8] studies involving 665,009 patients with psoriasis and 17,902,757 non-psoriatic control subjects were included for the meta analysis. The pooled analyses according to each cardiovascular outcome revealed that pooled RR of patients for developing myocardial infarction, stroke, cardiovascular death, ischemic heart disease, thromboembolism and arrhythmia were 1.17 (95% confidence interval [CI], 1.11–1.24), 1.19 (95% CI, 1.11–1.27), 1.46 (95% CI, 1.26–1.69), 1.17 (95% CI, 1.02–1.34), 1.36 (95% CI, 1.20–1.55) and 1.35 (95% CI, 1.30–1.40), respectively. Meanwhile, the pooled RR of patients with mild and severe psoriasis for developing adverse cardiovascular outcomes were 1.18 (95% CI, 1.13–1.24) and 1.41 (95% CI, 1.31–1.52), respectively. Conclusion The pooled analyses revealed that psoriasis is associated with all adverse cardiovascular outcomes of interest, especially in severe patients. Psoriasis remains an independent risk factor for adverse cardiovascular outcomes, which needs more attention from clinicians.